Juvenile cases of skeletal tuberculosis from the Terry Anatomical Collection (Smithsonian Institution, Washington, D.C., USA) - Pálfi, György (Acta Biologica Szegediensis, 2012)
In order to better define the variability of skeletal expression of tuberculosis, we studied 1728 skeletons from the Terry Anatomical Collection, Smitsonian Institution, dating from the first half of the 20th century. Among the numerous cases we studied there were three juvenile individuals who died from TB that are of particular interest. The spine of the first case exhibits lesions related to a multifocal cystic spondylitis, associated with rib lesions probably caused by a pneumo-pleural infection. The second skeleton has frontal and parietal endocranial lesions that can be attributed to TB meningitis. The associated multifocal vertebral and costal abnormalities apparent in this case may represent an early stage in the development of skeletal TB lesions. The skull vault of the third skeleton is perforated by lytic lesions compatible with a diagnosis of cranial tuberculosis. These lesions are associated with bone forming endocranial lesions that suggest TB meningitis. The postcranial skeleton shows mainly osteolytic lesions. These case-studies give an insight to different manifestations of skeletal TB and provide stronger basis for identifying this infection in archaeological human remains. The three juvenile skeletons from the Terry Anatomical Collection provide evidence that lesions like endocranial symptoms, vertebral hypervascularization, rib periostitis, diffuse periostitis of long bones and especially their association do have diagnostical value in the identification of tuberculosis.